2016
DOI: 10.1136/bmjopen-2016-011498
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pregnancy outcomes in Ghanaian women with varying dietary diversity: a prospective cohort study protocol

Abstract: IntroductionPoor dietary intake during pregnancy can have negative repercussions on the mother and fetus. This study therefore aims to explore the dietary diversity (DD) of pregnant women and its associations with pregnancy outcomes among women in Northern Ghana. The main outcome variables to be measured are gestational weight gain and birth weight.Methods and analysisA prospective cohort study design will be used and 600 pregnant women in their first trimester will be systematically recruited at health facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Each district has a district hospital, health centers and several Community-based Health Planning Services (CHPS) compounds depending on the size of the district [ 34 ]. Due to its position in the middle belt of Ghana, the Ashanti region was chosen for this study and also because the majority of maternal and child health studies have been conducted in both the Northern and Southern sectors of Ghana [ 31 , 35 ]. A rural area is a community with less than 5000 population while all others are considered urban [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each district has a district hospital, health centers and several Community-based Health Planning Services (CHPS) compounds depending on the size of the district [ 34 ]. Due to its position in the middle belt of Ghana, the Ashanti region was chosen for this study and also because the majority of maternal and child health studies have been conducted in both the Northern and Southern sectors of Ghana [ 31 , 35 ]. A rural area is a community with less than 5000 population while all others are considered urban [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, the indicator has been tested with regard to whether it is associated with socioeconomic characteristics ( 19 , 20 ). It has been used to explore linkages between diet and coronary artery disease ( 21 ), pregnancy-related outcomes ( 22 , 23 ), and child growth ( 24 ), but also to develop new metrics for food biodiversity in diets ( 25 ). In Bangladesh, it has begun to be used for program evaluation ( 26 ), and its applicability to pregnant adolescent girls and women has also been tested ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the pregnant women who consumed food with low diversity had increased chances of low birth weight babies compared to their counterpart. [16] A prospective cohort study conducted in Norway, found that both increased or decreased weight gain compared to IOM recommendations were associated with adverse fetal and pregnancy outcomes. The Odds ratio of low birth weight increased when the gestational weight gain is less than the IOM recommendations and odds ratio of large for gestational age, gestational diabetes, preecclampsia increased as the gestational weight gain is more than the IOM recommendations.…”
Section: Discussionmentioning
confidence: 99%